Safe Neighborhood for Adolescent Girls: The Case of Urban Dense Kampong In Yogyakarta City Center - Mu’afifah Mu’afifah; Setiawan Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Nowadays, the percentage of adolescents living in urban areas is increasing, including in Indonesia. Unfortunately, urban planning and design are very limited in involving the perspective of youth, including the provision of safe public space. This paper is concerned with understanding safe public spaces from the perspective of adolescent girls. This paper aims to explore whether the neighborhood, specifically its public spaces, according to the girls' perspective is safe enough by using a case study approach with the case of a dense organic neighborhood in the city of Yogyakarta, Kampong Code. The information was obtained by observation, forum group discussion (FGD), and also by conducting a safety walk with local adolescent girls. This paper found that although from a normative perspective, public spaces in the neighborhood are considered as not safe enough, because they were familiar with this condition, they tend to perceive that as a usual situation.